PENGARUH JENIS PEMERINTAH KABUPATEN/KOTA, JUMLAH PENDUDUK, DAN LUAS WILAYAH TERHADAP PERUBAHAN ANGGARAN DI MASA PANDEMI COVID-19 PADA PEMERINTAH KABUPATEN/KOTA DI PROVINSI ACEH - Muhammad Zul Achyar; Muhammad Saleh (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2023)
This study aims to examine the effect of the type of district/city government, total population, and area size on changes to district/city government budgets in Aceh in 2020 and 2021. The data used is secondary data from local government financial reports audited by the BPK RI (Badan Pemeriksa Keuangan Republik Indonesia), reports on changes to the budget obtained from BPKA (Badan Pengelola Keuangan Aceh), total population data from BPS (Badan Pusat Statistik), and area size data from the Directorate General of Population and Civil Registry of the Ministry of Home Affairs. The data analysis method used is the Multiple Linear Regression Test. The results showed that the area size and total population had a significant effect on budget changes, the type of district/city government did not affect changes to district/city government budgets in Aceh during the Covid-19, while the three independent variables simultaneously affected dependent variables. The Coefficient of Determination analysis result is 0.279, which means that the variable type of district/city government, total population, and area size can explain 27.9% of changes in district/city government budgets during the pandemic.